Science of Medicine in Ibn Khaldun's Thought - Krauss, Nurdeen Deuraseh Steven Eric (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Science of Medicine in Ibn Khaldun's Thought